Regulation of contextual conditioning by the median raphe nucleus - Avanzi, V; Castilho, V. M.; de Andrade, TGCS; Brandao, M. L. (Elsevier B.V., 1998)
The median raphe nucleus (MRN) has been suggested as the origin of a behavioral inhibition system that projects to the septum and hippocampus. Electrical stimulation of this mesencephalic area causes behavioral and autonomic manifestations characteristic of fear such as, freezing, defecation and micturition. In this study we extend these observations by analyzing the behavioral and autonomic responses of rats with lesions in the MRN submitted to a contextual conditioning paradigm. The animals underwent electrolytic or sham lesions of the median raphe nucleus. One day (acute) or 7 days (chronic) later they were tested in an experimental chamber where they received 10 foot-shocks (0.7 mA, 1 s with 20-s interval). The next day, sham and MRN-lesioned animals were tested again either in the same or in a different experimental chamber. During this, the duration of freezing, rearings, bouts of micturition and number of fecal boli were recorded. Sham-operated rats placed in the same chamber showed more freezing than rats exposed to a different context. This freezing behavior was clearly suppressed in rats with acute or chronic lesions in the MRN. MRN lesions also reduced the bouts of micturition and number of fecal boli. These rats showed a reduced number of rearings than sham-lesioned rats. This effect is probably the result of the displacement effect provoked by freezing since no significant differences in the number of rearings could be observed between these animals and the NMR-lesioned rats tested in an open field. This lesion produced higher horizontal locomotor activity in this test than the controls (sham-lesioned rats). These results point to the importance of the median raphe nucleus in the processing of fear conditioning with freezing being the most salient feature of it. Behavioral inhibition is also under control of MRN but its neural substrate seems to be dissociated from that of contextual fear. (C) 1998 Elsevier B.V. B.V.
Keywords: median raphe nucleus; freezing; fear conditioning; behavioral inhibition